Osnove diagnostične citopatologije - Strojan Fležar, Margareta (Medicinski razgledi, 2008)
Cytopathologic examination is a diagnostic method which encompasses light-microscopic examination of cells that exfoliate spontaneously from body surfaces or are obtained through various diagnostic procedures. Basic diagnostic evaluation of a diverse range of pathologic processes can be conducted by performing the cytopathologic examination of cells, most importantly for quick diagnosis of malignant neoplasms and its precursors. ThePap test which represents the cervical smear is the most common cytopathologic specimen used in screening programs for the early detection of precancerous lesions and cervical cancer. It is mandatory to obtain cell samples in accordance with professional guidelines, and to properly fix and accurately label them on the spot in order to make a reliable cytopathologic diagnosis. Laboratory procedures should be standardized and quality assurance and quality control measures should be implemented.
Keywords: Citodiagnostika; Cytodiagnosis; Neoplasms; Novotvorbe; tumor; Pathology